How's life? 2013 - Measuring well-being. - (:unkn) unknown (My University, 2013)
Every person aspires to a good life. But what does "a good or a better life" mean? The second edition of How's Life? paints a comprehensive picture of well-being in OECD countries and other major economies, by looking at people's material living conditions and quality of life across the population. In addition, the report contains in-depth studies of four key cross-cutting issues in well-being that are particularly relevant: how has well-being evolved during the global economic and financial crisis?; how big are gender differences in well-being?; how can we assess well-being in the workplace?; and how to define and measure the sustainability of well-being over time?
Keywords: Gesundheitswesen; Gesundheitspolitik; Gesundheitsrisiko; Vergleichsuntersuchung; Lebensbedingungen; Gesundheitsbericht; Internationaler Vergleich; Public Health; Ländervergleich